Distance Learning Barriers and Bottlenecks: A Phenomenological Inquiry on the Conduct of English Language Arts (ELA) Standard Assessments - Garbo, Jesselle M.; Lopres, Jaypee R.; Novenario, Melissa P.; Esternon, Cara Elijah G.; Pilapil, Gleiza Marie P.; Gomez, Bernadette L.; Silva, Mary Faith B.; Anjao, Rachel M. (International Journal of Learning, Teaching and Educational Research, 2023)
This phenomenological study explored the lived experiences of elementary English Language Arts (ELA) teachers in the United States of America concerning the distance learning barriers they faced in conducting standard assessments. Seven (7) participants were personally interviewed to gather the data using open-ended questions. Utilizing a cellular phone, all responses were recorded for transcription. Colaizzi’s method for data analysis was employed. After a rigorous analysis of the transcripts, the following twelve (12) themes arose to capture the teachers’ lived experiences: Frequent Absenteeism, Poor Sense of Accountability, Distracting Workspace, Insufficient Knowledge of Technology, Dearth of Motivation and Support, Glitches of Technology, Disparity in Data, Need for Backup, Perpetual Communication to Parents, Call to Differentiate Instruction, Workload Exhaustion, and Deficient Training Ground. The study concluded that the lived experiences of elementary ELA teachers are distinct and compelling. Some distance learning barriers are student absenteeism, parents’ non-participation, and the reliability of scores. The teachers were only partially convinced that scores were authentic, so they adopted creative ways to gather data to determine learning goals that needed to be addressed. Teachers faced barriers and bottlenecks, causing stress. ELA teachers remained hopeful, believing in overcoming barriers with passion. Administrators should support teachers in addressing online test challenges and emphasize parental involvement. Clear communication and reminders to students are crucial, while parents should minimize distractions and encourage focus during online assessments. Future research should focus on analyzing and addressing the setbacks that teachers experience when converting from on-site to online assessments. https://doi.org/10.26803/ijlter.22.8.3